Incidence of hyperthyroidism in patients with bipolar or schizoaffective disorder with or without lithium: 21-year follow-up from the LiSIE retrospective cohort study - Ingrid Lieber; Michael Ott; Robert Lundqvist; Mats Eliasson; Ursula Werneke (SAGE Publishing, 2023)
Background: Lithium-associated hyperthyroidism is much rarer than lithium-associated hypothyroidism. Yet, it may be of substantial clinical significance for affected individuals. For instance, lithium-associated hyperthyroidism could destabilise mood, mimic manic episodes and impact physical health. Only few studies have explored incidence rates of lithium-associated hyperthyroidism. Even fewer studies have compared incidence rates according to lithium exposure history. Objectives: To determine the impact of lithium treatment on the incidence rate of hyperthyroidism in patients with bipolar or schizoaffective disorder and assess its aetiology. Design: This study is part of the LiSIE (Lithium - Study into Effects and Side Effects) retrospective cohort study. Methods: Between 1997 and 2017, patients in the Swedish region of Norrbotten with a diagnosis of bipolar or schizoaffective disorder were screened for all episodes of overt hyperthyroidism in form of thyrotoxicosis or thyroiditis. Incidence rates of episodes of hyperthyroidism per 1000 person-years (PY) were compared in relation to lithium exposure; concurrent, previous, or no exposure ever (lithium-naïve patients) Results: In 1562 patients, we identified 16 episodes of hyperthyroidism corresponding to an incidence rate of 0.88 episodes per 1000 PY. Ninety-four percent of episodes had occurred in women. Patients who had concurrently been exposed to lithium, had an incidence rate of 1.35 episodes per 1000 PY. Patients who had previously been exposed to lithium had an incidence rate of 0.79 per 1000 PY. Patients who had never been exposed to lithium had an incidence rate of 0.47 per 1000 PY. There were no significant differences in the risk ratios for patients with concurrent or previous exposure compared with lithium-naïve patients, neither for hyperthyroidism overall, thyrotoxicosis, or thyroiditis. Conclusion: Lithium-associated hyperthyroidism seems uncommon. The risk of hyperthyroidism does not seem significantly higher in patients with current or previous lithium exposure than in lithium-naïve patients.